THE WORK PROFESSIONALISM OF EMPLOYEE IN PUBLIC SERVICES AT MENUR PUMPUNGAN VILLAGE OFFICE, SURABAYA CITY - Alvionita Pratama; Rachmawati Novaria; M. Kendry Widiyanto (MAP Observer: Jurnal Penelitian Administrasi Publik, 2023)
The role of employee work professionalism is largely determined by the level of ability of employees which is reflected through their daily behavior in the organization. The ability of employees to provide public services leads to the achievement of a company's goals that have been planned. The low quality of public services is due to the low professionalism of public officials in providing public services. Unprofessionalism of public officials in providing public services can lead to demands and cause the public (society) to be dissatisfied with the services provided by public officials. This research was conducted to know the Professionalism of Employees in Public Services at the Menur Pumpungan Village Office, Surabaya City. The research method used is a qualitative research method using observation data collection techniques and informant interviews. From the results of the analysis, it is known that the skills and responsibilities of employees in Menur Pumpungan Village, Surabaya City state that the implementation of public services, employee attitudes, and employee readiness are quite satisfactory. However, from the discipline in providing services, it is still considered unsatisfactory. Increasing the Professionalism of Employee Work to improve the quality of public services.